2021
DOI: 10.1063/5.0045675
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the permeability of regular polymeric networks by the cross-link ratio

Abstract: The amount of cross-linking in the design of polymer materials is a key parameter for the modification of numerous physical properties, importantly, the permeability to molecular solutes. We consider networks with a diamond-like architecture and different cross-link ratios, concurring with a wide range of the polymer volume fraction. We particularly focus on the effect and the competition of two independent component-specific solute–polymer interactions, i.e., we distinguish between chain-monomers and cross-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…In our previous work, we have obtained G ( z ) from simulations in equilibrium via where c eq ( z ) and are the penetrant’s equilibrium concentration profile and the bulk concentration, respectively. We observed that G ( z ) can be conveniently mapped on a piecewise step function given in eq . The mean plateau value of G ( z ) in the membrane, Δ G , defines our partition ratio (see Table ) via …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, we have obtained G ( z ) from simulations in equilibrium via where c eq ( z ) and are the penetrant’s equilibrium concentration profile and the bulk concentration, respectively. We observed that G ( z ) can be conveniently mapped on a piecewise step function given in eq . The mean plateau value of G ( z ) in the membrane, Δ G , defines our partition ratio (see Table ) via …”
Section: Resultsmentioning
confidence: 99%
“…The potential field G ( z ) constitutes the membrane as a finite energy barrier (or attractive well) in the system and originates from the microscopic interactions between penetrants and the membrane. We consider G ( z ) as an average potential field, which can be obtained from molecular simulations by Boltzmann-inverting the average equilibrium partitioning profile. The equilibrium diffusivity field D ( z ) also depends on the membrane and penetrant properties. Our system comprises two local diffusivities, D ( z ) = D 0 in the bulk and D ( z ) = D in in the membrane (see eq ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the membrane center of mass was tightly bound to the center of the simulation box (r center ), with the spring constant k com = 100 k B T /σ per membrane particles. The membrane thickness d(f ) is computed based on the full width at half maximum [99], which varies slightly with the force only for large P eq [see Fig. 3(c)], otherwise it is nearly constant (see Table I for the equilibrium d).…”
Section: A Simulation Setup and Protocolsmentioning
confidence: 99%
“…The bead-spring model of the polymeric network has also been used to simulate solute diffusion in gels. This coarse-grained model, employed to study gel swelling and solute partitioning from the early 2000s, allows us to explicitly consider crosslinked flexible polymer chains. ,, The model is particularly appropriate to explicitly consider solute–monomer and solute–crosslinker interactions or to simulate tightly meshed networks. , In addition, polydispersity or entanglements can also be implemented. , …”
Section: Introductionmentioning
confidence: 99%